Pertumbuhan Ekonomi Dan Ketimpangan: Dampaknya Terhadap Kemiskinan Di Indonesia - Irmawanti Irmawanti; Mohd Winario (Multidisciplinary Journal of Religion and Social Sciences, 2026)
Economic growth is one of the main indicators of a country’s development success, as it reflects increases in productive capacity and overall economic activity. However, high economic growth is not always accompanied by an equitable distribution of income. In Indonesia, economic inequality remains a structural problem that directly affects poverty levels and social welfare. This study aims to analyze the relationship between economic growth and income inequality and their impact on poverty in Indonesia. The research employs a descriptive and analytical approach using secondary data obtained from official institutions, such as Statistics Indonesia (Badan Pusat Statistik) and other relevant agencies. The findings indicate that uneven economic growth tends to widen income inequality and hinder poverty reduction. Conversely, inclusive economic growth, accompanied by a more equitable distribution of income and expanded access to economic opportunities, is proven to be more effective in reducing poverty. Therefore, development policies in Indonesia should be directed not only toward accelerating economic growth but also toward reducing inequality in order to achieve equitable and sustainable social welfare.